Re/producing the global middle class: International Baccalaureate alumni at 'world-class' universities in Hong Kong. Issue 5 (3rd September 2019) - Wright, Ewan; Lee, Moosung
ABSTRACT: This research investigated educational pathways into a Global Middle Class characterised by professional or managerial careers and cosmopolitan sensibilities. The focus was International Baccalaureate Diploma Programme (IBDP) alumni with upper-middle-class backgrounds at 'world-class' universities in Hong Kong. The first objective was to investigate if and how the education of IBDP alumni at Hong Kong universities shapes self-perceptions of cosmopolitan sensibilities, university experiences, and economic futures. The second objective was to investigate how the IBDP and Hong Kong universities offer an educational pathway for the existing Global Middle Class to reproduce their social position and for local families to enter the Global Middle Class. Interview findings illuminated how cosmopolitan sensibilities meant that the students may be well-positioned for careers and lifestyles of the Global Middle Class. Nevertheless, there were paradoxes of cosmopolitan sensibilities as the students perceived a lack of belonging to their universities and a disconnection with the local society.